Usage-based approaches to child code-switching: State of the art and ways forward - Gaskins, Dorota; Quick, Antje Endesfelder; Verschik, Anna; Backus, Ad (Cognitive Development, 2022)
Input-output effects have been the subject of keen research for several decades in the study of monolingual acquisition from a usage-based perspective (Ambridge & Lieven, 2011). However, for bilingual acquisition, similar studies are only beginning to emerge. One major challenge for such studies is to explain why young children switch between their two languages (e.g., Ich bin ready ‘I am’ ready) even when they hear no such switching in their input. This article reviews a strand of recent studies in children aged two to three to explain this apparent paradox. It demonstrates how the focus on one aspect of input, the child's own prior speech, can explain how and why code-switching occurs. The article examines a range of psycholinguistic processes, showing how they drive variation in children's use of mixed utterances. Its main contribution lies in its summative value and the recommendations made for future research in early code-switching.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Child code-switching; Chunking; Frequency; Priming; Segmentation; Usage